2007
DOI: 10.1097/mnm.0b013e3280964eae
|View full text |Cite
|
Sign up to set email alerts
|

The value of quantifying 18F-FDG uptake in thyroid nodules found incidentally on whole-body PET–CT

Abstract: Focally high uptake of 18F-FDG in the thyroid as an incidental finding occurred in 1.1% of the patients. Malignancy was confirmed or was suspicious in 17/48 (35%) of the patients that had adequate follow-up. There was no significant difference in the SUVmax between benign and malignant nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
53
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 22 publications
7
53
1
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] In contrast, diffuse, bilateral FDG-PET uptake is usually associated with benign disease (Table 3) In the current study, the prevalence of cancer was 30% (9/30) for those in whom a confirmed cytologic or histologic diagnosis was obtained via FNAC or surgery, and this incidence was similar to that reported by others. [3][4][5][6][7][8][9][10][11] The overall incidence of cancer in the current series was relatively low at 8.7% (9 of 103). Because more than half of the patients with PETomas (53 of 103) did not undergo further evaluation with either ultrasonography, FNAC or surgery, the true prevalence of cancer is arguably underestimated.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…[3][4][5][6][7][8][9][10][11] In contrast, diffuse, bilateral FDG-PET uptake is usually associated with benign disease (Table 3) In the current study, the prevalence of cancer was 30% (9/30) for those in whom a confirmed cytologic or histologic diagnosis was obtained via FNAC or surgery, and this incidence was similar to that reported by others. [3][4][5][6][7][8][9][10][11] The overall incidence of cancer in the current series was relatively low at 8.7% (9 of 103). Because more than half of the patients with PETomas (53 of 103) did not undergo further evaluation with either ultrasonography, FNAC or surgery, the true prevalence of cancer is arguably underestimated.…”
Section: Discussionsupporting
confidence: 86%
“…[3][4][5][6][7][8][9][10][11] Moreover, the prevalence of malignancy within these PETomas is remarkably high at 14%-56%. [3][4][5][6][7][8][9][10][11] In contrast, diffuse, bilateral FDG-PET uptake is usually associated with benign disease (Table 3) In the current study, the prevalence of cancer was 30% (9/30) for those in whom a confirmed cytologic or histologic diagnosis was obtained via FNAC or surgery, and this incidence was similar to that reported by others. [3][4][5][6][7][8][9][10][11] The overall incidence of cancer in the current series was relatively low at 8.7% (9 of 103).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations